Au/TiO2–gC3N4 Nanocomposites for Enhanced Photocatalytic H2 Production from Water under Visible Light Irradiation with Very Low Quantities of Sacrificial Agents. Issue 14 (24th January 2018) - Marchal, Clément; Cottineau, Thomas; Méndez‐Medrano, María Guadalupe; Colbeau‐Justin, Christophe; Caps, Valérie; Keller, Valérie
Abstract: Here for the first time the design and optimization are presented of a three‐component Au/TiO2 –gC3 N4 nanocomposite photocatalyst able to efficiently produce H2 from water using very low amounts of sacrificial agents and under visible light irradiation. This enhanced photocatalytic behavior compared to Au/TiO2 and Au/gC3 N4 materials is the result of synergetic effects due to high quality assembly and interface between the three components. This optimized nanoscale assembly characterized by simultaneous favorable nanoheterojunction formation between g‐C3 N4 and TiO2 semiconductors, as well as AuNPs/gC3 N4 and AuNPs/TiO2 junctions, leads to enhanced visible light harvesting, charge separation, and H2 production. This composite photocatalyst yields a high H2 production (350 µmol −1 h −1 gcatalyst −1 ) under visible light irradiation with minimal amounts of sacrificial agent (≤1 vol%), corresponding to activities much higher than reported so far under comparable conditions. Abstract : A optimized combination of TiO2, g‐C3 N4, and Au nanoparticles within a composite material enables highly efficient photocatalytic H2 production from water under visible‐light with low amounts of sacrificial agents. The high quality assembly and contact between the three constituents result in a synergetic effect leading to better visible light absorption and better use of the photogenerated charge carriers.